PENGARUH LITERASI KEUANGAN, PREFERENSI RISIKO, DAN MOTIVASI TERHADAP PERILAKU INVESTOR PEMULA - Veggy Pradasari; Irianing Suparlinah; Mafudi * (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
This research is a quantitative research with a survey method entitled "The Influence of Financial Literacy, Risk Preference and Motivation on Beginner Investor Behavior". The population in this study was the entire investor community in Purwokerto. The samples were taken using purposive sampling, namely 104 investors who can be sampled because they have met the existing criteria. Retrieval of data using the online questionnaire method with google form media. The data analysis technique in this study is multiple linear regression, by testing the coefficient of determination, F test and t test. Based on data analysis, the results showed that: (1) financial literacy has a positive effect on the behavior of novice investors, (2) risk preference has no effect on the behavior of novice investors, (3) motivation has a positive effect on the behavior of novice investors. The implication of this research is that financial literacy and motivation are fundamental for novice investors. That way, there is a capital market seminar or training needed so that novice investors have good financial literacy, especially in finance to support them. In addition, as a novice investor who has high motivation to invest, he will get more benefits from the future. The higher the level of financial literacy and motivation, the better the behavior in making investment decisions in the capital market. As well as students as investors should choose investment instruments according to risk preferences.